1999
DOI: 10.1530/jrf.0.1170387
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine-induced premature oestrus is associated with changes in the pulsatile secretion pattern of follicle-stimulating hormone in beagle bitches

Abstract: The secretory profiles of LH and FSH were investigated before and during the administration of bromocriptine in six beagle bitches. Plasma samples were obtained via jugular venepuncture at 10 min intervals for 6 h every 2 weeks until the next ovulation. Bromocriptine treatment was started 100 days after ovulation. Both before and after bromocriptine treatment, LH and FSH pulses occurred together. The mean duration of the FSH pulse (120 min) was significantly longer than that of the LH pulse (80 min). The inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…The high GnRH secretion associated with MPA treatment postulated in the previous paragraph may therefore have resulted in desensitization of the response of the gonadotropes to GnRH. The decline to pretreatment FSH levels and the decrease in responsiveness of pituitary FSH secretion to GnRH are probably part of the estrus-preventing effects of MPA, because increased FSH secretion is a critical event in the initiation of ovarian folliculogenesis [46,47]. In other words, MPA treatment for estrus prevention may prohibit the normal rise in plasma FSH concentration during late anestrus.…”
Section: Discussionmentioning
confidence: 99%
“…The high GnRH secretion associated with MPA treatment postulated in the previous paragraph may therefore have resulted in desensitization of the response of the gonadotropes to GnRH. The decline to pretreatment FSH levels and the decrease in responsiveness of pituitary FSH secretion to GnRH are probably part of the estrus-preventing effects of MPA, because increased FSH secretion is a critical event in the initiation of ovarian folliculogenesis [46,47]. In other words, MPA treatment for estrus prevention may prohibit the normal rise in plasma FSH concentration during late anestrus.…”
Section: Discussionmentioning
confidence: 99%
“…The decline in prolactin concentration is not the key event triggering anoestrus termination. This appears to be a consequence of other central dopaminergic effects shown by cabergoline but not by other antiprolactin drugs, like metergoline, acting as secotonin antagonists (Kooistra et al. 1999a).…”
Section: Discussionmentioning
confidence: 99%
“…The administration of some dopamine agonists, like bromocriptine or cabergoline, is associated with an increase in basal plasma FSH concentration, resulting in the shortening of the interoestrus interval (Okkens et al. 1997; Kooistra et al. 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…61 In healthy young men manipulating hormonal levels to decrease prolactin with cabergoline increases sexual desire and arousal in laboratory conditions. 62 It has been reported that [63][64][65] cabergoline could reduce the length of anestrous and induce a fertile estrous period in bitches. Improved penile erections and libido caused by dopaminergic compounds occaSalvage of sildenafil failures with cabergoline MR Safarinejad sionally can be perceived as adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…For question 4, the mean score was 3.7 (51.4% increase from baseline mean score of 1.8) for the cabergoline group compared with 2 (20% increase from baseline mean score of 1.6) for the placebo group. At the 6-month end point, 64 Salvage of sildenafil failures with cabergoline MR Safarinejad at sexual intercourse in the cabergoline group as compared with 6% successful attempts during placebo treatment (P ¼ 0.02). Data from patients' event logs showed no evidence of a treatment period effect.…”
Section: Efficacymentioning
confidence: 99%